Teaching Speaking of Narrative Text through Storytelling to the Tenth Graders in MAN 2 kota Kediri (RETAIN, 2014)
Teaching Speaking of Narrative Text through Storytelling to the Tenth Graders in MAN 2 kota Kediri Mokhamad Gufron English Education, Faculty of Languages and Arts, State University of Surabaya ghufronman@gmail.com Fauris Zuhri, S.Pd., M.Hum. English Education, Faculty of Languages and Arts, State University of Surabaya Abstract Based on the objective of study of English in senior high school, the students have to master narrative text in speaking skill. Since narrative text mostly in form of stories, storytelling is applied in English speaking classroom to enable them to speak narrative. Since the research is descriptive qualitative, it would describe the phenomenon that is teaching speaking of narrative text through storytelling in which the students are in the tenth grade of senior high school. The researcher conducts the observation and the questionnaire to get the data. The data is also obtained from the students’ speaking assessment task. From the result of the research, storytelling which is applied in narrative speaking classroom is engaging for the students. Most of the students are enjoyable to learn speaking through storytelling. Thus, most of their ability in narrative speaking through storytelling is good. In conclusion, the researcher finds that storytelling is a suitable technique to teach narrative speaking to the students; moreover the students are interested in learning speaking through storytelling. Abstrak Berdasarkan pada tujuan pembelajaran bahasa Inggris di Sekolah Menengah Atas (SMA), siswa harus menguasai teks naratif dalam kemampuan berbicara. Karena teks naratif sebagian besar dalam bentuk cerita, storytelling digunakan dalam kelas berbicara bahasa inggris supaya siswa mampu berbicara secara naratif. Oleh karena penelitian ini adalah deskriptif kualitatif, penelitian ini akan menggambarkan fenomena pengajaran berbicara teks naratif dengan bercerita dimana para siswa adalah siswa-siswi kelas X SMA. Peneliti melakukan observasi dan menggunakan kuesioner untuk mendapatkan data. Selain itu data juga didapat dari tugas berbicara siswa. Dari hasil penelitian, storytelling yang diaplikasikan di kelas berbicara naratif adalah menarik bagi siswa. Sebagian besar siswa menikmati belajar berbicara dengan storytelling. oleh karena itu kemampuan mereka dalam berbicara naratif adalah baik. Pada kesimpulannya, peneliti mengemukakan bahwa storytelling adalah teknik yang tepat untuk mengajar berbicara naratif kepada siswa. Lebih dari itu, siswa tertarik pada pembelajaran berbicara dengan storytelling. INTRODUCTION Students of senior high school have to master several genres in the end of teaching and learning activity. It means that they have to master those genres in language skills including speaking. One of the genres which is learned is narrative text. According to Anderson, narrative text tells about something happened in the past, and its purpose is to amuse the reader. Conducting an oral activity should be done in careful ways because not all students are experienced in speaking English. The problem may arise in the initiation of the performance, perhaps it is difficult to get started students to speak. The students who unconfident might be fail because they are afraid of making mistake, here the teacher should emphasis that making mistake in learning is a natural matter. Due to the factors which influence speaking, storytelling is implemented to teach narrative speaking in the classroom to encourage the students to speak. As stated by Davis (2007:4) storytelling grew from the playful elements of human nature and satisfied a need for self-entertainment. Moreover the students are familiar with storytelling because it has been existed in the culture since long ago, records in storytelling have been found in many ancient cultures and languages, including Sanskirt, Old German, Latin, Chinese, Greek, Iceland, and Old Slavonic (Davis, 2007:3). That is why using storytelling is an effective way to teach narrative text. Speaking is the natural language which is used most by people in daily life. Thornbury also defines speaking as speech production which takes place in real time and is therefore essentially linier. Talking about speaking is something important however based on history, language teaching concerned more on written language than speaking language (Brown and Yule, 1983). Moreover Brown and Yule also stated that the function of speaking is drawn from two basic language functions, these are transactional function which is primarily concerned with the transfer of information, and the interactional function in which the primarily purpose of speech is the maintenance the social relationship. There are two forms of speaking, those are monologue and dialogue. Nunan (1989:27) points out that monologue speaking which is the ability to give an uninterrupted oral presentation is quite distinct than interacting with one or more than other speakers for transactional and interactional purpose. It means that not all the speakers are able to speak monologue well without any preparation even though they are native speaker. According to brown and Yule frame work in Richard (2008:21) there are three different functions of speaking namely talk as interaction, talk as transaction and talk as performance. Talk as performance refers to public talk, that is talk to transmit information before an audience, such as classroom presentations, public announcements and speeches. It tends to be in form of monolog rather than in dialog, often follows a recognizable format (e.g., a speech of welcome), and is closer to written language than conversational language (Richards, 2008:27). Teaching talk as performance a different strategy, as stated by Jones in Richards (2008: 35), initially, talk as performance needs to be prepared for and scaffold in much in the same way of written text, and many of the teaching strategies used to make understanding of written text accessible can be applied to the formal uses of spoken language. Good speaking activities can and should be extremely engaging for the students. If they are participating fully – and if the teacher has set up the activity properly and can then give sympathetic and useful feedback – they will get tremendous satisfaction from it (Harmer, 2007: 123). According to Richard (2003:214), there are three techniques in teaching speaking that make the students improve their ability to produce target language acquires many verbal nuances, improve their ability to work cooperatively in group situation, and effectively deal affective issues, those are storytelling, drama and role-play. Pellowski in Davis (2007:4) defines storytelling is the art or craft of narration of stories in verse and or prose, as performed or led by one person before a live audience, the stories narrated may be spoken, chunted or sung, with or without musical, pictorial, and / or other accompaniment, and may be learned from oral, printed, or mechanically from recorded sources, one of its purposes may be that of entertainment. Since storytelling can be part of an integral part of everyday life, it seems only natural that our students should have or would like to have opportunities to share their own experiences to their friends and classmates as well (Edwards and Willis, 2005:201). Stories are natural because people in society always have stories to be told, this is a good factor for the students to experience storytelling in their families because it will enrich the knowledge of stories. As stated by Anderson and Anderson (2003) that narrative text is a text that tells a story and, in doing so to entertain the audience. Anderson and Anderson (2003) also said that there are five generic structures in constructing a narrative text. They are orientation, complication, a sequence of events or evaluation, resolution, and coda. There are some language features of narrative stated on 2006 National Curriculum, it said that narrative focuses on the specific participants, it usually uses past tense, there are temporal conjunction, there are many action verb and direct and indirect sentences are often used. METHOD This research is qualitative. Mackey and Gass (2005:162) Briefly defined, that qualitative research can be taken to refer to research that is based on descriptive data that does not make (regular) use of statistical procedure. There were two subjects of the study. The first one was the English teacher of class X-I in MAN 2 kota Kediri. The second subject was the students of class X-I in MAN 2 kota Kediri. The class consisted of 24 students, there were 6 male students and 18 female students. There were three research instruments to obtain the data, the first is observation checklist, it was used to observe all the teacher’s and students’ activity during the class. Since this observation would be a non-participatory observation. The second was students’ speaking assessment task, to get the score of the students’ speaking ability, the researcher will analyze the students’ speaking task. The task itself is in audio-video form, that is why the students were asked to record their speaking task using video cameras. Furthermore, the recording would be analyzed to describe the students’ speaking ability. The third instrument was questionnaire, The type of the questionnaire is closed item questionnaire, as stated by Nunan (1992:143), a close item is one in which the range of possible responses is determined by the researcher. The data will be analyzed qualitatively in descriptive way, it means that the researcher would explain it through the use of words. Moreover, there would be three stages in analyzing the data. The first stage is selecting and identifying data, the second stage was displaying data, and the last stage was drawing conclusion. RESULT AND DISCUSSION The observation had been done in three meetings. In the first meeting, the teacher gave an example how to do storytelling. after that he asked some students to retell the story in front of the classroom, he also explained the generic structure of narrative text in the end of teaching and learning activity. At the second meeting, he asked all the students to practice the storytelling, then he gave correction and evaluation to the students’ performance. At the third meeting, the teacher explained the language features of narrative text. According to Davis (2007) the most important part is determining the story, the teacher here choose the existing story to tell, he prepared story very well. The teacher gave the example of the story orally at the beginning of the learning processes. He intended to be a model of a storyteller in front of the students. By giving an example of storytelling at the beginning, the teacher tried to encourage the students to express the feeling in speaking activity. That is why while he was telling the story he performed it in attractive ways by expressing in appropriate voice, gestures and facial expression. It is in line with the procedure of telling story by Davis (2007) that a storyteller has to consider three important factors, they are voice, expression, movement and posture. However the learning process mainly about speaking activity, the teacher had explained the gist and the characteristic of narrative text to the students. Thus the generic structure and the language feature of the text were elaborated from the spoken text they had been learning. This is in line with the next instruction of the teacher which asked the students to retell the storytelling contained those generic structure and language feature. Students’ speaking assessment task was in form of video recording of the students’ storytelling. The video recording showed the students’ speaking ability. There were four samples which represent four criteria of students’ ability. The student who got excellent mark comprehended the story very well. From the content of the story, she could tell the events in chronological order. She also told the orientation, complication and resolution accurately, it showed that she understood the generic structures of the text accurately. Almost of her sentences were well constructed, only there are few mistakes such as “it means the movie will start”. The student’ pronunciation was also clear and accurate. that is why the story was very understandable. Moreover on the recording, her performance was almost perfect, she could tell the story with showing appropriate mimic and expression. That is why this storytelling is excellent. The student who got good score comprehended the story well, it could be seen from its chronological order. Unfortunately, there were few mistakes in constructing of correct pieces of language, the mistake was in the use of past tense, she sometimes used present tense to tell the story, such as “They want to marry her, but the king have one solution”, also there were another mistake in constructing sentence as follows “Finally the Mountain God will be the winner and can marry the princess”. The pronunciation and fluency were fair because she often spoke with hesitation. The student who got average score has average ability in constructing sentences. From the content, its orientation and complication are quite good, but the resolution is not clearly understandable. In telling the story, this student also lack of gesture and facial expression, but his pronunciation is almost correct. The student who got poor score did not comprehend the story well, it could be seen from the orientation that difficult to be understood. The sentences that she made also difficult to be understood because almost all sentences contain mistake in constructing of correct piece of language. For example “the ten sun in sky other something”, there is no verb used in that sentence, that is why it is understandable. Then there were many mistakes in pronunciation, such as in the sentence “there were ten suns in sky”, the pronunciation of “were” should be /wɜ:ʳ/, but her pronunciation is incorrect by pronounce it /weəʳ/. The word sky should be pronounced /skaɪ/, but she pronounced /skɪ/. In the sentence “many people were dead” the word dead should be pronounced /ded/, but she pronounced /dɪd/, those mistakes made different meaning of those sentences. Also in fluency, the student spoke with hesitation which disturbs the communication. Based on the scoring instrument of speaking task, there was one student got excellent score, the student who got excellent score was able to perform storytelling with almost no mistake in miming, understand the generic structure appropriately, speak without hesitation, no mistake in accuracy and pronunciation, and use a variety of vocabulary. Other 14 students got good score, the students who got good score have the ability to tell story with few mistakes in miming and generic structures, they speak with some hesitation with few mistakes in constructing correct piece of language, also they have clear pronunciation but made some errors in word choices. Other 8 students got average score. These students were able to tell the story with many mistakes in miming but few mistakes in generic structures, they speak with some hesitation and there are many mistakes in accuracy. The pronunciation is unclear, sometimes difficult to understand, they also use limited vocabulary. Only one student who got poor score, she has lack ability to show mimic and expression she also could not tell the generic structures clearly, she speaks with often hesitation and almost all sentences contain mistakes in accuracy, she also has frequent problem in pronunciation and uses only basic vocabulary. This is not surprisingly most of the students got very good score, it because they had been doing the exercise before they perform it, moreover the students did the storytelling in form of video recording which meant they did the storytelling freely outside of the classroom with less obstacle. The result of the questionnaire would describe the students’ response toward the teaching technique. The questions in the questionnaire were classified into six focuses. The first two questions showed that the students were interested to learn narrative text, but they were not so interested to learn speaking skill. The result showed that learning speaking skill was something uninterested for the students. That is why the teacher has to find out the creative learning activity to attract the students’ response to learn. The result of the next four questions that focused on classroom speaking activity showed that most of the students were interested in storytelling by the teacher in the classroom, but they were not so interested to actively participating in storytelling in the classroom. It showed that the students needed more feedback when they were having speaking activity in the classroom. It might be the students lack of confident to express storytelling which necessary good gesture and facial expression. The result of next three questions showed that all the students tend to like more familiar story in their life. Obviously, telling familiar stories from their own culture is easier than others. The teacher at that time told the story from abroad, it might make the students get difficulties in comprehending the story. The result of the next five questions showed that most of the students enjoyed having storytelling activities. The teacher kept on encouraging the students to speak by giving opportunity to each student to practice storytelling. The result of the next three questions showed that the students were comfortable with the teacher’s role in the classroom,. As in the speaking classroom, the teacher always supports the students by giving enjoyable activity for speaking. The last three questions showed that the students expected they would be able to enhance their ability in speaking by storytelling. On the overall activity, the students enjoyed storytelling activity to enable their narrative speaking. CONCLUSION Teaching speaking of narrative text through storytelling is initiated by selecting what story to tell to the students. Then the teacher has to be a role model how to be a good storyteller. The teacher also explained the generic structure of narrative story by having discussion with the students. By giving example how to perform the storytelling, in the whilst activity, the students were expected to be able to perform it without any obstacle. To get the students’ understanding of the language feature of narrative text, the teacher also explained the language feature which is used in the story in the post activity. From the result of students’ speaking assessment task, it can be concluded that one of the students is excellent in their storytelling, most of them are good in their storytelling and some of them are average in their storytelling. From the discussion on the students’ response, it can be concluded that the students were interested with the story performed by the teacher, but they tend to like the story which is familiar in their daily life. They also enjoyed the storytelling activities in the classroom with the role of the teacher who a support them, they also expected that storytelling would be able to enhance their ability in speaking. For overall conclusion, it can be concluded that the students enjoyed storytelling to enable their narrative speaking. REFERENCES Anderson, M & Anderson, K. 2003. Text Types in English 2. Australia: Macmillan Education Australia PTY LTD. Brown, G & Yule, G. 1989. Teaching the Spoken Language: An Approach based on The Analysis of Conversational English. Cambridge: Cambridge University Press. Davies, Alison. 2007. Storytelling in the Classroom: Enhancing Oral Traditional Skills for Teachers and Pupils. London: Paul Chapman Publishing. Depdiknas. 2006. Kurikulum 2006: Standar Kompetensi Mata Pelajaran Bahasa Inggris Sekolah Menengah Atas dan Madrasah Aliyah. Jakarta: Depdiknas. Edwards, C. & Willis, J. 2005. Teachers Exploring Tasks in English Language Teaching. New York: Palgrave MacMillan. Harmer, Jeremy. 2007. The Practice of English Language Teaching Fourth Edition. Edinburgh: Pearson Education Limited. Mackey, Allison & Gass, S.M. 2005. Second Language Research. Methodology and Design. New Jersey: Lawrence Elbraum Associates Inc. Nunan, David. 1989. Designing Task for the Communicative Classroom. Cambridge: Cambridge University Press. Nunan, David. 1992. Research Methods in Language Learning. Cambridge: Cambridge University Press. Richards, J.C. & Renandya, W.A. 2002, Methodology in Language Teaching. An Anthology of Current Practice. New York: Cambridge University Press. Thornbury, Scott. 2005. How to Teach Speaking. Edinburgh: Pearson Education Limited.